Exploring the Connectivity Between Education 4.0 and Classroom 4.0: Technologies, Student Perspectives, and Engagement in the Digital Era - Kapil Joshi; Rajesh Kumar; Salil Bharany; Dilip Kumar Jang Bahadur Saini; Rajiv Kumar; Ashraf Osman Ibrahim; Abdelzahir Abdelmaboud; Wamda Nagmeldin; Mohammad Awad Medani (IEEE Access)
The democratic welfare government is equally committed to quality-driven, impartial, and egalitarian education. The major contribution of this study is to examine the problems and opportunities posed by the incorporation of digital technology in the classroom via the lens of Classroom 4.0 (CLSR4) and education 4.0. The commitment of the democratic welfare government to equitable and quality education is investigated, in line with the Global Agenda SDG 4 goal of ensuring comprehensive and lifelong education for everyone. The modern classroom is witnessing a clash between traditional teaching methods and the digital competency of today’s tech-savvy generation. The goal of this study is to examine the connections between education 4.0 and classroom 4.0 by looking at developments in classroom architecture and the use of digital platforms. The biggest issue found is instructors’ inability to adjust to changing conditions. In terms of methodology, confirmatory factor analysis is used in this work to investigate the dynamics of correlations in the context of Classroom 4.0. This method offers insights into the variables influenced by metaverse technology, resulting in a thorough comprehension of the evolving educational scene. This study’s findings shed insight into how students see the changing classroom and the role that various platforms play in engaging them. The study underscores the need for educators to effectively integrate these tools and address this digital transformation to improve teaching and learning experiences. However, there are study constraints, most notably the limited contextual scope, which is exclusively focused on the Indian educational setting. Further research in other worldwide contexts is required to generalize the findings. In the future, it is critical to investigate and build creative instructional practices that effectively synergize with Classroom 4.0. Furthermore, further research should be conducted to determine how governments and educational institutions might adapt to this paradigm shift, ensuring a smooth and effective transition into the digital era of education.